Uterine Dysfunction in Diabetic Mice: The Role of Hydrogen Sulfide - Emma Mitidieri; Domenico Vanacore; Carlotta Turnaturi; Raffaella Sorrentino; Roberta d'Emmanuele di Villa Bianca (MDPI AG, 2020)
It is well-known that the physiological uterine peristalsis, related to several phases of reproductive functions, plays a pivotal role in fertility and female reproductive health. Here, we have addressed the role of hydrogen sulfide (H2S) signaling in changes of uterine contractions driven by diabetes in non-obese diabetic (NOD) mice, a murine model of type-1 diabetes mellitus. The isolated uterus of NOD mice showed a significant reduction in spontaneous motility coupled to a generalized hypo-contractility to uterotonic agents. The levels of cyclic nucleotides, cAMP and cGMP, notoriously involved in the regulation of uterus homeostasis, were significantly elevated in NOD mouse uteri. This increase was well-correlated with the higher levels of H2S, a non-specific endogenous inhibitor of phosphodiesterases. The exposure of isolated uterus to L-cysteine (L-Cys), but not to sodium hydrogen sulfide, the exogenous source of H2S, showed a weak tocolytic effect in the uterus of NOD mice. Western blot analysis revealed a reorganization of the enzymatic expression with an upregulation of 3-mercaptopyruvate-sulfurtransferase (3-MST) coupled to a reduction in both cystathionine-β-synthase (CBS) and cystathionine-γ-lyase (CSE) expression. In conclusion, the increased levels of cyclic nucleotides dysregulate the uterus peristalsis and contractility in diabetic mice through an increase in basal H2S synthesis suggesting a role of 3-MST.